PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Almunaf, Dhiaz Indrazaprila; Tjiptodjojo, Kartika Imasari (FEB Universitas Sam Ratulangi Manado, 2024)
Understanding quality services and products in a business is one of the factors that needs attention, especially in dealing with rapidly changing trends. Moreover, changes in trends are closely related to changes in consumer behavior. Consumers will easily switch purchases if they feel dissatisfied. Therefore, this study examines how service quality and product quality can influence purchasing decisions made by consumers. Data shows that despite an increase in coffee consumption in Indonesia, Kintsugi Terrace sales have fluctuated, with a significant decline from August to November 2024. Data collection involved 97 respondents selected through non-probability with purposive sampling. The results show that simultaneously service quality and product quality have a significant positive effect on purchasing decisions by 66.7%.